2006
DOI: 10.1128/iai.74.4.2373-2381.2006
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Ca BIG1 Gene Reduces β-1,6-Glucan Synthesis, Filamentation, Adhesion, and Virulence in Candida albicans

Abstract: The human fungal pathogen Candida albicans is able to change its shape in response to various environmental signals. We analyzed the C. albicans BIG1 homolog, which might be involved in ␤-1,6-glucan biosynthesis in Saccharomyces cerevisiae. C. albicans BIG1 is a functional homolog of an S. cerevisiae BIG1 gene, because the slow growth of an S. cerevisiae big1 mutant was restored by introduction of C. albicans BIG1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Therefore, a ␤-1,6-glucan inhibitor is expected to remove these proteins from the cell and reduce the pathogenesis of C. albicans as a result. In fact, there are several reports suggesting that C. albicans mutants with a reduced level of ␤-1,6-glucan are avirulent (16,45). Our study clearly shows a potent inhibitory effect of D75-4590 against hyphal elongation as well.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, a ␤-1,6-glucan inhibitor is expected to remove these proteins from the cell and reduce the pathogenesis of C. albicans as a result. In fact, there are several reports suggesting that C. albicans mutants with a reduced level of ␤-1,6-glucan are avirulent (16,45). Our study clearly shows a potent inhibitory effect of D75-4590 against hyphal elongation as well.…”
Section: Discussionsupporting
confidence: 65%
“…[ 14 C]glucose (Daiichi Pure Chemicals, Tokyo, Japan) was added to a cell suspension at a concentration of 2 Ci/ml. At each time point, a 10-ml sample was taken and crude fractions of ␤-1,3-glucan, chitin, mannan, and ␤-1,6-glucan were prepared based on the method of Umeyama et al (45). The harvested cells were suspended in 2 ml of 3% NaOH and heated for 1 h at 80°C.…”
Section: Strainsmentioning
confidence: 99%
“…Taken together, our study demonstrated that Spf1 is essential for maintenance of cellular calcium homeostasis under ER stresses and high-level calcium conditions. In C. albicans, hyphal cells contain more chitin and b-1,6-glucan, and less mannoproteins than yeast cells, indicating a link between hyphal development and cell wall composition, which is dependent on cell wall protein homeostasis (Herrero et al, 2004;Umeyama et al, 2006). Our study showed that the spf1D/D mutant had a significant defect in hyphal development.…”
Section: Role Of Spf1 In Candida Albicansmentioning
confidence: 61%
“…␤-1,6-Glucan synthesis and incorporation proceed through several enzyme steps (14), and Fks1p inhibition would affect a late stage. Our finding is consistent with suggestions from gene disruption studies (6) and studies of glucose linkages in Cryptococcus neoformans (7) and broadens our understanding of caspofungin antifungal mechanisms.…”
mentioning
confidence: 99%